Research of Meshing Characteristic of Positive Modified Gear based on Finite Element Method - Wang Hongzhen; Ma Xiaoying (Jixie chuandong)
The changing of meshing stiffness will lead to vibration and reduce the stability of the gear drive. By using Abaqus general analysis step and implicit dynamic analysis step,the meshing process of elastic and rigid gear pair of shear cutting department are calculated respectively. In MATLAB,the three-coordinate plot is applied to analyze the stress characteristics of gear pair in the whole meshing process. The Mises stress of tooth profile at different meshing positions and moments are calculated. The maximum contact press,the maximum Mises stress and their positions during meshing are calculated. The results show that the varying meshing stiffness caused the angular displacement deviation fluctuation during the static meshing of gear pair,in addition,the fluctuation of driven gear angular velocity lead to larger fluctuation of angular displacement deviation during dynamic meshing of gear pair. The change of load and the change of meshing stiffness caused the fluctuation of angular velocity deviation of driven gear. The methods and references for gear design and research of shear cutting department are provided by this study.